Synthesis and modification of TiO2 and WO3 based nanostructured materials for environmental applications - Thind, Sapanbir Singh (My University, 2015)
TiO2 and WO3 based nanomaterials are highly attractive for various applications encompassing photocatalysis, electrochromic devices, dye sensitized solar cells, hydrogen production, and sensing applications due to their low cost, non-toxicity, high efficiency, chemical inertness and ability to be synthesized in various morphologies. TiO2 is the most intensely studied photocatalyst and a significant proportion of research focuses on improving its photocatalytic activity, which is innately limited due to its wide band gap and electron/hole recombination kinetics. The doping and co-doping of metals and non-metals into the crystal lattice of TiO2 have proved to reduce the band gap and decrease the rate of electron/hole recombination. This band gap reduction results in absorptive red shifting, which may be utilized for visible light-driven photocatalysis and dye sensitized solar cells (DSSC). Although WO3 is a very promising material that has the capacity for absorbing in the visible spectrum, it pales in comparison to TiO2 in terms of efficacy and thus there are considerable opportunities for the improvement of its activity for various applications through its modification. During my PhD study, mesoporous N-doped and N,W co-doped TiO2 photocatalysts were initially prepared with an exclusive anatase phase and high specific surface areas, utilizing a facile, reproducible and inexpensive solution combustion synthesis method. The atomic percentage of N was kept constant, whereas that of W was varied from 0.5% to 3% in order to evaluate the effects of the amount of W on the photocatalytic activities and other properties of the materials. It was observed that the N and W atoms were well incorporated into the titania lattice structure, which led to a significant red shift in the absorption edge of the co-doped TiO2, and concordantly, a dramatic narrowing of the band gap. Photodegradation studies of rhodamine B (RhB) dye on the various samples revealed that an enhancement of up to 14 fold in the reaction rate was observed with 1.5 at% W doped TiO2 as compared with commercial Degussa P25. To enhance the activity of the TiO2 based materials we introduced a novel UV treatment approach. The UV treated electrodes exhibited a dramatic increase in the donor density of the TiO2 nanotubes by three orders of magnitude. For the UV treated electrodes the photocurrent was enhanced 15 fold and the photoelectrochemical activity was approximately 6.8 times higher than that of the untreated TiO2 nanotubes. This novel approach was also employed with the N, W II co-doped mesoporous TiO2. Following the UV treatment, the photocatalytic activity of the co- doped samples was increased two-fold under UV light and a 12-fold under visible light. The increase in the activity of the TiO2 nanotubes and N, W co-doped samples may be attributed to the lowering of the band gap due to the formation of Ti3+ during the UV treatment process. Next, WO3 platelets were grown on W substrate via a hydrothermal method. The WO3 nanoparticles prepared at 180 °C over one hour heat treatment demonstrated the best photocurrent, and as the duration of the heat treatment was increased, the photocurrent commenced to decrease. The WO3 prepared at 180 °C over three hours showed minimal photocurrent. To elucidate crystal growth kinetics, for the first time, an electrochemical reduction method was utilized, which revealed that the plate-like structures originated from an arrayed nanosphere layer that resided beneath them. Interestingly, the obtained layer of nanospherical WO3 demonstrated high photocurrent and photocatalytic activity under UV-Vis light. To optimize the photocatalytic activity of the WO3, as well as the electrocatalytic activity of the Pt nanoparticles, so-called bifunctional electrodes were prepared. The Pt nanoparticles that were deposited on one side of the WO3 electrodes served as an electrocatalyst, while the opposite side, consisting of the WO3 platelet like structures, was employed as the photocatalyst. The results indicated that the synthesized WO3 electrodes possessed considerable activity when exposed to visible light, while the deposition of the Pt significantly enhanced the activity of the electrode. An overall enhancement in the catalytic activity was noticed for bifunctional electrodes when electrocatalyst and photocatalyst were activated together, in contrast to the case where photocatalysis and electrocatalysis were employed separately. Moreover, the platelet WO3 surfaces were modified with Ta2O5, IrO2 and IrO2-Ta2O5 thin films for energy storage. To the best of our knowledge, no previous study has articulated the utilization of IrO2-Ta2O5 as supercapacitors. Our results revealed that when Ta2O5 and IrO2 were employed concomitantly on the WO3 surface, they exhibited a synergistic effect, where the capacitance measured for this electrode was much higher than that of the Ta2O5 or IrO2 containing electrodes. These electrodes demonstrated high stability in which the 5000th charge/discharge cycle was identical to that of the initial cycle. 3 In summary, the photocatalysts and electrocatalysts developed in this PhD study exhibited high activity in the abatement of various pollutants, as well as for energy storage. Our results indicated that the performance of the catalyst was contingent, to a significant degree, on the dimensions, morphologies and electronic structures of the nanostructured materials. The solution combustion method for co-doping TiO2 and UV treatment approach, developed in this study were shown to be rapid, reproducible and easily amenable to scale-up, thus creating potential opportunities for the fabrication of high-performance TiO2 and WO3 nanomaterials in myriad beneficial environmental applications.
Keywords: Catalysis; Photocatalysis; Nanostructured materials; Tungsten oxides; Titanium dioxide; Environmental aspects